Essays on women in earliest Christianity ; v.2 - Osburn, Carroll D. (Joplin, MS College, 1995)
Includes bibliographical references, Scripture index and other indexes.
Keywords: Women -- Biblical roles; Women -- early church -- ca.30-600.